Being with other animals: Transitioning toward sustainable food futures - Nieuwland, Joachim; Meijboom, Franck L. B. (Frontiers in Sustainable Food Systems, 2023)
How do nonhuman animals (hereafter animals) fit into sustainable food futures? This question prompts ethical reflection. However, especially in times of transformative change, one should not overlook ontological assumptions before engaging in ethics. We follow up on the work of the late Australian philosopher Val Plumwood as she prominently made this move to the ontological level when considering the edibility of animals. As she invites one (1) to listen to animals as well as (2) to embody one’s own edibility, salient ontological assumptions about how humans relate to other animals, and the rest of reality, rise to the surface. While Plumwood also developed a modest ethical framework to address animal edibility, her ontological approach is highlighted here, especially as it appears to point towards moral relativism. Plumwood’s ontological approach is further developed, notably by unraveling the dualism between self and other. Doing so results in a more non-conceptual way of relating to other animals. As a genuinely interdependent way of engaging with reality, it appears most relevant to considering what role animals might have in sustainable food futures.